INCLUSIVE ECONOMIC GROWTH ANALYSIS OF CITIES IN NORTH SULAWESI - Gaby Dainty Julliet Roring; Een Novritha Walewangko (Jurnal Equilibrium, 2023)
National development strives to achieve high economic growth. However, high economic growth does not guarantee high inclusiveness of development. Economic growth must be inclusive and sustainable to create more extensive access and opportunities for all levels of society equitably, improve welfare, and reduce inequalities. This research used secondary data of economic growth, poverty, unemployment, and gini ratio in 2018 – 2022 period of cities in North Sulawesi. Inclusive Growth Index (IGI) is used to measure inclusive economic growth. The results of the analysis show that in 2018 – 2022 period, inclusive growth towards poverty in Manado is still non inclusive, while in Bitung, Tomohon and Kotamobagu is inclusive. Inclusive growth towards unemployment in Manado and Kotamobagu is non inclusive and inclusive in Bitung and Tomohon. Inclusive growth towards gini ratio in Tomohon, Bitung and Kotamobagu is inclusive, while in Manado is non inclusive.